Founder of the Kazakhstan school of civil studies (Dedicated to the 100th anniversary of Yuri Grigorievich Basin) (Journal of actual problems of jurisprudence, 2023)
The article deals with the formation and development of the science of civil law in Kazakhstan during the Soviet period and during the years of independence of the republic. The significant role in the creation of the Kazakh school of civil law of Yuri Grigoryevich Basin, Honored Scientist of Kazakhstan, Doctor of Law, Professor, is emphasized. These legal issues are understudied in Kazakhstan, and this isthe scientific novelty of this article. The subject of the study of the article is the formation and development of the science of civil law in Kazakhstan. The purpose of the article is to show the stages of formation and direction of scientific research of representatives of the legal school of civil law in Kazakhstan in the Soviet period and the independent period of the republic. The methodological basis of the studywas a historical analysis of the activities of scientific teams of the republic in the field of development of the science of civil law in Kazakhstan. During the Soviet period, two significant scientific teams were formed in the republic – at the Faculty of Law of the Kazakh State University and at the Institute of Philosophy and Law of the Academy of Sciences of the Kazakh SSR. Many scientific problems were solved by these collectives by common forces. It should be noted that in 1991 on the basis of the Institute of Philosophy and Law, the Institute of State and Law of the National Academy of Sciences of the Republic of Kazakhstan was established.With the acquisition of independence by Kazakhstan, a number of leading civil scientists began to work at the Kazakh State Law University and the Research Center for Private Law created under it. In the future, the Academy of Law – the Higher School of Law “Adilet”, in 2007 became part of the Caspian Public University. The Research Institute of Private Law began to work as part of the Higher School of Economics “Adilet”. Key words: science of civil law, history, higher education, scientific teams, functions of science, dissertations on civil law, codification of civil legislation, educational works, theoretical works, Sovietperiod, independent period.